Epilepsy as a Presenting Symptom of Covid-19 in a Tertiary Private Hospital in Northern Mexico - Sofía Lucila Rodríguez Rivera; José Antonio Infante Cantú; Héctor R. Martínez; Enrique Caro Osorio (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Various manifestations of COVID-19 have been described in patients, including neurological. Few studies describe seizures as a presenting symptom. This study was aimed to identify clinical characteristics, type of epilepsy and electroencephalographic findings in patients with epilepsy as a presenting symptom of COVID-19 in a tertiary private hospital. Methods. Descriptive, retrospective, observational and cross-sectional study. Inclusion criteria were patients with epilepsy as a presenting symptom of COVID-19 confirmed with Polimerase Chain Reaction (PCR) for SARS-CoV2 by nasopharyngeal swab from March 2020-July 2021 in a tertiary private hospital. Study variables were age, gender, type of epilepsy, comorbidities and electroencephalographic findings. It was classified into three groups: acute symptomatic seizures, onset of epilepsy, and uncontrolled epilepsy. Information was captured in Excel and analyzed in SPSS. Results. Of 203,987 patientes with a confirmed diagnosis of COVID-19 in Nuevo León until July 2021, 10 patients (0.004%) were included with seizures. Two patients had acute symptomatic seizures (20%), four patients had onset seizures (40%) and four patients (40%) had uncontrolled epilepsy with an average epilepsy evolution time of 15.75 years. Focal seizures were predominant in 63%. Electroencephalogram was abnormal in 90% (50% focal frontotemporal sharp waves, 20% encephalopathic, 20% generalized spike wave). Two patients (20%) had status epilepticus. Conclusion. This study is important in order to carry out early detection in suspects or with a previous neurological history and to avoid the spread of the coronavirus.